Histological characteristics of the largest and secondary tumors in radical prostatectomy specimens and implications for focal therapy - Young Hyo Choi; Ji Woong Yu; Byong Chang Jeong; Seong Il Seo; Seong Soo Jeon; Hyun Moo Lee; Hwang Gyun Jeon (BMC, 2019)
Abstract Background Pathological features of prostate cancer in Korean men were analyzed to determine whether identification of tumor volume, Gleason score (GS), focality, and location using radical prostatectomy (RP) specimens can provide useful information for the application of focal therapy (hemiablation). Methods From January 2016 to December 2017, 913 patients who underwent RP at a single center were selected for analysis. Patients with prostate-specific antigen levels > 15 ng/mL or those who had received hormone therapy prior to surgery were excluded. Preoperative data and the number, volume, location, and GS of each tumor were recorded. Results Overall, 762 RP specimens were examined, and 1448 tumors were identified. The majority of the cases were multifocal (60.5%) and bilateral (82%) in nature. Among the 686 secondary tumors, 250 (36.4%) had a GS ≥7 and 122 (17.8%) had a tumor volume ≥ 0.5 mL. Among the 435 bilateral multifocal cases, secondary tumors on the lobes contralateral to the largest tumor were significant by volume (≥0.5 mL) in 91 (20.9%) cases and by grade (GS ≥7) in 179 (41.1%) cases. There were 102 (23.4%) tumors with a small tumor volume (< 0.5 mL) and Gleason pattern 4 on the lobe contralateral to the largest tumor. Conclusions Bilateral and multifocal tumors are a common feature and secondary tumors frequently exhibit clinically significant prostate cancer on RP specimens in Korea. In many cases, secondary tumors on the lobe contralateral to the largest tumor had a high GS and small tumor volume.